Hydrological approaches to measure or estimate crop water use – B. Practical application - Carrilho, Vasco (2024)
We present an application in which the time sequence of the differences between the estimated values of soil water content (SWC or θ) and the measured ones, in this case by the most direct method of gravimetry, provided an opportunity to exemplify the possibility of adjusting a selected parameter used for actual evapotranspiration (ETa) estimation. The variable selected for adjustment was the crop coefficient (Kc), for which one finds a higher uncertainty. This is a simple self-learning process, in the sense that the investment, in obtaining correct soil parameters and soil water data of good quality, creates an opportunity to get well-adjusted parameters for better ETa estimation that, used in the following, allows a better irrigation scheduling. The stress coefficients were also estimated. The crop used is pepper (Capsicum annuum L.), planted in a field located in center-east Portugal, in a clay loam soil, drip irrigated, using different spacing arrangements (simple and double line) and occasional stress periods in some of the four experimental plots. The values of Kc resulting from this kind of iterative process were quite different from the initial ones, and relatively well related with leaf area index measured in the four plots.